Negative Reinforcement and Premonitory Urges in Youth With Tourette Syndrome: An Experimental Evaluation. (March 2014) - Capriotti, Matthew R.; Brandt, Bryan C.; Turkel, Jennifer E.; Lee, Han-Joo; Woods, Douglas W.
Tourette syndrome (TS) is marked by the chronic presence of motor and vocal tics that are usually accompanied by aversive sensory experiences called "premonitory urges." Phenomenological accounts suggest that these urges occur before tics and diminish following their occurrence. This has led some to suggest that tics are negatively reinforced by removal of premonitory urges. This hypothesis has proven difficult to test experimentally, however, due in part to challenges in measuring premonitory urge strength. We tested predictions of the negative reinforcement conceptualization of premonitory urges using novel experimental tactics within the context of the "tic detector" paradigm. We compared tic rates and ratings of premonitory urge strength exhibited by youth with TS or chronic tic disorder under free-to-tic baseline (BL), reinforced tic suppression (RTS), and reinforced tic suppression with escape (RTS + E) conditions. Results were consistent with previous research and hypotheses of the present study. Participants rated the strength of their premonitory urges as higher during RTS conditions than during BL conditions. Within RTS + E conditions, tic rates were higher during escape portions when the contingency supporting tic suppression was inactive than during components where the contingency was active, and ratings of urge strength were higher at the onset of break periods than at the offset. All participants engaged in some level of escape from reinforced suppression during the course of the experiment. Results of this study support the notion that tics may be negatively reinforced by removal of aversive premonitory urges. Future directions for basic and clinical research are discussed.